2013
DOI: 10.5430/jnep.v4n2p132
|View full text |Cite
|
Sign up to set email alerts
|

A mixed-methods approach to evaluating student nurses changing answers on multiple choice exams

Abstract: Using a mixed methods approach, the purpose of this study was to examine the perceptions and patterns of nursing student's changing answers on multiple choice exams. The sample of 86 students enrolled in an undergraduate nursing program were surveyed after their first exam of the semester. Exam response forms were examined for erasure marks to determine the answer changes on the exam grade; additionally, the relationship between self-reported school performance and frequency of changing answers, and self-repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“… 10 , 11 , 22 , 23 Students who may have made a careless mistake or who remembered exam content as the exam progressed are also more likely to benefit from changing their answers. 10 , 17 , 24 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 10 , 11 , 22 , 23 Students who may have made a careless mistake or who remembered exam content as the exam progressed are also more likely to benefit from changing their answers. 10 , 17 , 24 …”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for the observed trend is that low performing students who have less understanding of the material have less confidence in their answer choices. Cox-Davenport et al 17 observed that students who had partial understanding of the material felt uncertain about their initial response and often narrowed down potential answers without feeling confident in their chosen answer choice. If a student does not fully understand the subject material and does not have confidence in his/her answers, they are more likely to change answers more frequently due to feeling anxious about his/her answer choices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a common belief that the first response to the test items is correct in the test and the second choice is incorrect if the response is changed later. Although test participants have worries about changing responses, they persistently change their responses (Cox-Davenport, Haynes, & Lawson, 2014). Therefore, the effect of RCB on test scores has always been a matter of interest.…”
Section: Response Change Behaviour (Rcb) In Testsmentioning
confidence: 99%
“…When the deleted markings or choices in the open-ended, true-false and MCTs made with paper and pencil items were examined, it was found that there was a general increase in the test scores of test participants (Al-Hamly & Coombe, 2003;Baştürk, 2011;Beck, 1978;Cox-Davenport, Haynes, & Lawson, 2014;Kim, 2019;Lynch & Smith, 1972). Only Noorbala and Mohammadi (2011) explained that RCB had a negative effect on test scores in a study conducted with medical students.…”
Section: Response Change Behaviour (Rcb) In Testsmentioning
confidence: 99%